QFT-based robust controller design for three-phase PWM AC to DC voltage source converter - Su, Chang Yi. (2008)
In this research, the design of QFT-based robust controller for the robust control of a three-phase PWM ac to dc converter is investigated. The objectives are: 1) To apply the QFT for robust control of a three-phase PWM ac to dc converter. 2) To study the effect of converter parameters on the system performance and robustness.